Gerakan Informatika Cerdas Berliterasi "berinovasi membangun peradaban diera 4.0 dengan budaya literasi" - Kholida Ismatulloh; Jamaluddin Jamaluddin; Baiq Desi Dwi Arianti; Rasyid Hardi Wirasasmita; Yosi Nur Kholisho; Muhammad Zamroni Uska; Heri Kuswanto; Ahmad Fathoni; Samsul Lutfi (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
Literacy ability teaches students to be diligent in reading and writing. In this case, teacher creativity is needed in determining effective and efficient ways. Elementary school is the basis for learning literacy because elementary school is the beginning of a child learning to read and write. Due to the current situation of Covid-19, students have not been able to study at school effectively and regularly. The teaching-learning process is carried out online, and students are asked to understand the use of information technology such as Android cell phones. The students moved to provide teaching by increasing the literacy culture of students with the help of technology as a medium to support their learning, without having to forget the importance of reading and writing from their textbooks. The resulting activities are digital literacy activities and learning while playing, where students are tasked with connecting information to their group members. The results obtained by the students became more enthusiastic and interested in learning such as reading and writing lessons because they were presented attractively on the display of media and learning videos.